Systemic Lupus Erythematosus Outpatients Medication Knowledge and Quality of Life - Maria Caecilia Nanny Setiawati; Nyoman Kertia; Ika Puspitaningrum (Universitas Sebelas Maret, 2023)
According to the Indonesian Lupus Foundation (YLI) in the last decade, the number of people with SLE (Systemic Lupus Erythematosus) has continued to increase every year. This research was undertaken to assess the medication knowledge and quality of life among SLE outpatients who had been counselled by pharmacist. A cross-sectional, non-experimental, descriptive study design was used in this research. A total of 121 respondents from Semarang and Yogyakarta met the criteria. Seventy (57,85%) respondents had previous counseling, while 51 (42,15%) respondents never. Their knowledge score was 32,17 ± 3,52 and the quality of life was 59,23 ± 17,04. There was any correlation between the knowledge score and their quality of life. *P 0,014. Their average age was 31,53 ± 7,77 years. It was positively related with their Quality of life *P 0,031 but not to their knowledge score. The participants’ education level and disease duration were not considerably related with QoL and knowledge. Previous counseling by the pharmacists was positively related to their knowledge score, but not to their quality of life (*P 0,034 and 0,793). The conclusion that can be drawn is the SLE outpatients had low knowledge and their quality of life is not good enough. Pharmacists’ counseling can improve SLE outpatients’ knowledge scores significantly but not their QoL.